Exposure to Alumina Nanoparticles in Female Mice During Pregnancy Induces Neurodevelopmental Toxicity in the Offspring - Zhang, Qinli; Ding, Yong; He, Kaihong; Li, Huan; Gao, Fuping; Moehling, Taylor J.; Wu, Xiaohong; Duncan, Jeremy; Niu, Qiao (Frontiers in Pharmacology, 2018)
Alumina nanoparticles (AlNP) have been shown to accumulate in organs and penetrate biological barriers which lead to toxic effects in many organ systems. However, it is not known whether AlNP exposure to female mice during pregnancy can affect the development of the central nervous system or induce neurodevelopmental toxicity in the offspring. The present study aims to examine the effect of AlNP on neurodevelopment and associated underlying mechanism. ICR strain adult female mice were randomly divided into four groups, which were treated with normal saline (control), 10µm particle size of alumina (bulk-Al), 50nm and 13nm AlNP during entire pregnancy period. Aluminum contents in the hippocampus of newborns were measured and neurodevelopmental behaviors were tracked in the offspring from birth to 1-month of age. Furthermore, oxidative stress and neurotransmitter levels were measured in the cerebral cortex of the adolescents. Our results showed that aluminum contents in the hippocampus of newborns in AlNP-treated groups were significantly higher than those in bulk-Al and controls. Moreover, the offspring delivered by AlNP-treated female mice displayed stunted neurodevelopmental behaviors. Finally, the offspring of AlNP-treated mice demonstrated significantly increased anxiety-like behavior with impaired learning and memory performance at 1 month of age. The underlying mechanism could be related to increased oxidative stress and decreased neurotransmitter levels in the cerebral cortex. We therefore conclude that AlNP exposure of female mice during pregnancy can induce neurodevelopmental toxicity in offspring. To our best knowledge, this study is the first investigation regarding neurodevelopmental toxicity of AlNP and warrants further studies to address potential neurodevelopmental toxicity associated with nanoparticles.